The Cultural Politics of European Prostitution Reform Governing Loose Women - Mattson, Greggor; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
The Cultural Politics of European Prostitution Reform traces case studies of four European Union countries to reveal the way anxieties over globalization translates into policies to recognize sex workers in some countries, punish prostitutes' clients in others, and protect victims of human trafficking in them all.
Keywords: Social policy; Sociology; Welfare state; Political sociology; Ethnology-Europe.; Sports-Sociological aspects